Predictability of oppositional defiant disorder and symptom dimensions in children and adolescents with ADHD combined type - GILL, MICHAEL (Cambridge University Press, 2010)
Background Oppositional defiant disorder (ODD) is frequently co-occurring with attention deficit hyperactivity disorder (ADHD) in children and adolescents. Because ODD is a precursor of later conduct disorder (CD) and affective disorders, early diagnostic identification is warranted. Furthermore, the predictability of three recently confirmed ODD dimensions (ODD-irritable, ODD-headstrong and ODD-hurtful) may assist clinical decision making. Method Receiver-operating characteristic (ROC) analysis was used in order to test the diagnostic accuracy of the Conners' Parent Rating Scale revised (CPRS-R) and the parent version of the Strength and Difficulties Questionnaire (PSDQ) in the prediction of ODD in a transnational sample of 1093 subjects aged 5?17 years from the International Multicentre ADHD Genetics study. In a second step, the prediction of three ODD dimensions by the same parent rating scales was assessed by backward linear regression analyses. Results ROC analyses showed adequate diagnostic accuracy of the CPRS-R and the PSDQ in predicting ODD in this ADHD sample. Furthermore, the three-dimensional structure of ODD was confirmed by confirmatory factor analysis and the CPRS-R emotional lability scale significantly predicted the ODD irritable dimension. Conclusions The PSDQ and the CPRS-R are both suitable screening instruments in the identification of ODD. The emotional lability scale of the CPRS-R is an adequate predictor of irritability in youth referred for ADHD.
PUBLISHED
Keywords: Neuroscience; ADHD